PROFIL IDEAL GURU BAHASA ARAB: SEBUAH KAJIAN TENTANG KOMPETENSI PEDAGOGIK DALAM PERSEPEKTIF AS-SUNNAH - Uswatul Jannah; Misnatun; Laylatul Jamila (Institut Kariman Wirayudha Sumenep, 2024)
This research starts from a number of problems regarding the professionalism of Arabic teachers from a pedagogical perspective as well as the idealization of these standards in the As-Sunnah review. Today's teaching profession must meet several requirements to be called an ideal teacher. Apart from academic qualifications, a teacher must have four competency standards, namely pedagogical competence, professional competence, personality competence and social competence. Each competency plays a significant role and function in realizing national education goals, where the four are considered as a reference for how teachers should be able to hold the ideal title. Because a number of these competencies require in-depth understanding, the researcher chose pedagogical competencies to be discussed further and then understood carefully. The research uses qualitative descriptive analysis with a library research approach which relies on reliable sources related to discussion variables, such as books, scientific journals, articles, magazines and the like which can support the validity of the research. After conducting an in-depth, detailed and specific study of the pedagogical terms contained in the Sunnah, interpretation is carried out through stages which include collection, reduction, presentation and drawing conclusions, as well as data verification. The results of the research show that the ideal pedagogical competencies that every educator must have as stated in the Sunnah are divided into several things, including including insight and educational background of teachers, understanding of students, developing curriculum and syllabi, designing, organizing learning, use of technology. learning, evaluating learning outcomes, and developing student potential.Keywords: Pedagogical competence, Arabic language teacher, As-Sunnah